2003
DOI: 10.1002/app.12464
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization kinetics of linear bimodal–polyethylene (LBPE) and LBPE/low‐density polyethylene blends

Abstract: Nonisothermal crystallization kinetics of linear bimodal-polyethylene (LBPE) and the blends of LBPE/ low-density polyethylene (LDPE) were studied using DSC at various scanning rates. The Avrami analysis modified by Jeziorny and a method developed by Mo were employed to describe the nonisothermal crystallization process of LBPE and LBPE/LDPE blends. The theory of Ozawa was also used to analyze the LBPE DSC data. Kinetic parameters such as, for example, the Avrami exponent (n), the kinetic crystallization rate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
3
0
4
Order By: Relevance
“…Another reason is that at a given temperature the crystallization processes with different cooling rates are at different stages, i.e., lower cooling rate processes are toward the end of the crystallization process, whereas at the higher cooling rate, the crystallization process is at an early stage. Although Ozawa's approach can be used to describe the non-isothermal crystallization behavior of low density polyethylene (LDPE), [23] the variation in the slope with temperature means that the parameter n is not a constant during crystallization and that Ozawa's approach is not a good method to describe the non-isothermal crystallization process of HDPE/EOC blends. As reported by Eder and Wlochowicz [24] the Ozawa equation is not valid for linear PE because of a high degree of secondary crystallization.…”
Section: Non-isothermal Crystallization Kineticsmentioning
confidence: 99%
“…Another reason is that at a given temperature the crystallization processes with different cooling rates are at different stages, i.e., lower cooling rate processes are toward the end of the crystallization process, whereas at the higher cooling rate, the crystallization process is at an early stage. Although Ozawa's approach can be used to describe the non-isothermal crystallization behavior of low density polyethylene (LDPE), [23] the variation in the slope with temperature means that the parameter n is not a constant during crystallization and that Ozawa's approach is not a good method to describe the non-isothermal crystallization process of HDPE/EOC blends. As reported by Eder and Wlochowicz [24] the Ozawa equation is not valid for linear PE because of a high degree of secondary crystallization.…”
Section: Non-isothermal Crystallization Kineticsmentioning
confidence: 99%
“…For bead processes, including foaming, blending is a practical way to manipulate the microstructural behavior of the materials to suit specifications. But, as observed in DSC thermograms [7][8][9][10][11][12][13][14][15][16][17][18][19][20], a blend's thermal behavior can differ significantly compared with that of its constituent components, although material types and weight ratios remain influential. For example, it has been found that adding an amount of less than 25% by weight ratio of low-molecular-weight linear polyethylene to linear-low-density polyethylene (LLDPE) promotes dual peaks generated in a DSC curve [9,10], whereas a high amount of over 40% by weight ratio of EVA added to LLDPE promotes dual peaks [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the branch content of LLDPE was shown to have a noticeable effect on the blend's crystallization behavior; the higher the branch content, the higher the possibility of dual peak creation [9,13,14]. When a bimodal polyethylene was used in a blend with a wider blending ratio [19,20], a higher tendency to create dual peaks was observed. The heating rate can also affect DSC endothermic thermogram behaviors, so that at a rate of greater than 58C/min, multiple peaks can appear or can be more distinct [9,10,16].…”
Section: Introductionmentioning
confidence: 99%
“…Pojêcie [1,2]. Obie wymienione frakcje [4], wy-stêpuj¹ce jednoczeoenie w równych stê¿eniach, powinny ró¿niae siê zdecydowanie modalnymi wartooeciami ciê¿aru cz¹steczkowego M 1 oraz M 2 , co pozwala na otrzymanie polimeru o bimodalnym rozk³adzie ciê¿aru cz¹steczkowego (rys. 1).…”
unclassified
“…1). Dwie mieszalne jego frakcje tworz¹ mieszaninê kompatybiln¹, o czym oewiadczy pojedynczy pik topnienia, oznaczany metod¹ analizy DSC [4].…”
unclassified